2004
DOI: 10.1002/pola.20214
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property correlations of sulfonated polyimides. I. Effect of bridging groups on membrane properties

Abstract: A series of six‐membered sulfonated polyimides were synthesized using 1,4,5,8‐naphthalenetetracarboxylic dianhydride, 4,4′‐diaminobiphenyl 2,2′‐disulfonic acid as the sulfonated diamine, and various nonsulfonated diamine monomers having different bridging groups. These bulky bridging groups have the capacity to increase hydrolytic stability and proton conductivity. Polyimides with bulky bridging groups showed increased solubility but exhibited lower thermal stability. The ion exchange capacity and water uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 27 publications
0
64
0
Order By: Relevance
“…One attractive class of alternatives for Nafion ® is sulfonated high performance condensation polymers, including poly(arylene ether ketones) [2][3][4][5], poly(arylene ether) [6,7], poly(arylene ether sulfones) [8][9][10], and polyimides [11][12][13][14]. These polymers were prepared from both direct polymerization of sulfonated monomers and post-sulfonation on polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…One attractive class of alternatives for Nafion ® is sulfonated high performance condensation polymers, including poly(arylene ether ketones) [2][3][4][5], poly(arylene ether) [6,7], poly(arylene ether sulfones) [8][9][10], and polyimides [11][12][13][14]. These polymers were prepared from both direct polymerization of sulfonated monomers and post-sulfonation on polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Lee et al have reported on the water stability up to 110 h at 80 C for their BDSA-based SPI membranes. 19,20 Recently, the research group of Mercier and Diat et al has reported on the aging of the BDSA-based block copolyimide membranes in PEFCs and in hot water. 21,22 The predominant aging mechanism was imide group hydrolysis, which was significantly accelerated above 80 C. These results lead us to the view that a series of copolyimide membranes derived from NTDA, BDSA and different nonsulfonated diamines generally have poor water stability at temperatures above 80 C. This review presents an overview of the synthesis, membrane stability, chemical and electrochemical properties, and fuel cell applications of new protonconducting polymer electrolyte membranes based on sulfonated polyimides that have been made during the past decade.…”
mentioning
confidence: 99%
“…25,26 From the WAXD results described previously, it is anticipated that DGEBA/BMH2 with relatively higher molecular ordering will show higher thermal stability than DGEBA/BMH1. However, TGA results showed the opposite result.…”
Section: Properties Of Cationically Cured Epoxy Resinsmentioning
confidence: 97%